493 Cohort study of osteoporosis and fracture risk: are we achieving benefit with secondary prevention?. (1st September 2016) - Davies, Llion; Berridge, Damon; Lyons, Jane; Walters, Angharad; Lyons, Ronan A
Abstract : Background: Osteoporosis is a global disease with a 30–40% lifetime risk of associated fractures according to the World Health Organisation. Osteoporosis incidence is likely to rise with ageing populations. Risk factor modification and medical treatments may reduce fracture risk. This work aimed to investigate the time to second fracture of patients receiving medical secondary prevention following index fracture compared to those that did not. Methods: An observational study design involved the formation of an anonymised e-cohort utilising linked records. All low impact fractures in patients aged >60 years were identified from the Secure Anonymised Information Linkage database between 01/04/2009 and 31/12/2014. Index and secondary fractures were identified from the emergency department and inpatient data sets. Linkages were made to censor for migration and mortality. Linked primary care records identified patients that had received prescriptions for fracture prevention medications. Statistical analysis involved regression models with accelerated time adjustments. Results: Over 49, 000 cases were included. Of these, 8, 033 (16.1%) had received medical treatment, the median age was 78 years (range 60–108) and 14, 120 (28.4%) were male. Receiving medical treatment was significantly associated with increasing age (OR 1.02, 95% CI: 1.017–1.022, p < 0.001) and female gender (p < 0.001). Secondary prevention was significantly and independently associated with lower hazard of second fracture (HR 0.25, 95% CI: 0.15–0.41, p < 0.001). Conclusions: Secondary medical prevention was associated with a 75% reduction in the hazard of sustaining a second fracture. However, fewer than a fifth of patients received such treatment. Study limitations include selection bias and potential residual confounding as patients were not randomised. Future work should focus on groups most likely to benefit from secondary prevention treatment to better inform clinical practice.